PROSPECTS FOR COKE BREEZE RECOVERY - D. N. Mihnovets; K. P. Dubinyak (Литьë и металлургия)
Researches give grounds to believe in the possibility of receiving briquettes from coke waste mixed with peat dry coal and their use for smelting iron in the cupola or as a household fuel.